Current and future burden of breast cancer: Global statistics for 2020 and 2040. (December 2022) - Arnold, Melina; Morgan, Eileen; Rumgay, Harriet; Mafra, Allini; Singh, Deependra; Laversanne, Mathieu; Vignat, Jerome; Gralow, Julie R.; Cardoso, Fatima; Siesling, Sabine; Soerjomataram, Isabelle
Abstract: Background: Breast cancer is the most commonly diagnosed cancer worldwide, and its burden has been rising over the past decades. In this article, we examine and describe the global burden of breast cancer in 2020 and predictions for the year 2040. Methods: Estimates of new female breast cancer cases and deaths in 2020 were abstracted from the GLOBOCAN database. Age-standardized incidence and mortality rates were calculated per 100, 000 females by country, world region, and level of human development. Predicted cases and deaths were computed based on global demographic projections for the year 2040. Results: Over 2.3 million new cases and 685, 000 deaths from breast cancer occurred in 2020. Large geographic variation across countries and world regions exists, with incidence rates ranging from <40 per 100, 000 females in some Asian and African countries, to over 80 per 100, 000 in Australia/New Zealand, Northern America, and parts of Europe. Smaller geographical variation was observed for mortality; however, transitioning countries continue to carry a disproportionate share of breast cancer deaths relative to transitioned countries. By 2040, the burden from breast cancer is predicted to increase to over 3 million new cases and 1 million deaths every year because of population growth and ageing alone. Conclusion: Breast cancer is the most common cancer worldwide and continues to have a large impact on the global number of cancer deaths. Global efforts are needed to counteract its growing burden, especially in transitioning countries where incidence is rising rapidly, and mortality rates remain high. Highlights: With over 2.3 million new cases and 685, 000 deaths in 2020, breast cancer is the most commonly diagnosed cancer worldwide. Most cases occur in transitioned countries yet transitioning countries have disproportionate share of breast cancer deaths. The future burden of breast cancer is predicted to increase to over 3 million new cases and 1 million deaths in 2040.